Kegiatan Edukasi dan Deteksi Dini Insomnia pada Kelompok Lanjut Usia di Panti Werda Hana - Alfred Sutrisno Sim; Biromo, Anastasia Ratnawati; Sugiharto, Hans; Syarifah, Andini Ghina; Kurniawan, Junius (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
Insomnia affects 30-50% of the adult population in the United States, with 5-15% experiencing chronic symptoms. Insomnia is characterized by dissatisfaction with the quality or quantity of sleep, insomnia presents challenges such as difficulty initiating, maintaining, and waking early, and is common in older adults. The Hana Nursing Home hosted this activity, with 61 participants in attendance. In this activity, there were 9 elderly people with mild and moderate insomnia respectively (14.75%) and 5 people (8.2%). Therefore, comprehensive clinical evaluation in the form of education and early detection is essential for effective clinical management of insomnia. Keywords: Insomnia, Education, Early detection